A clinical appraisal of the genetic basis in unexplained male infertility - Sandro C Esteves (Journal of Human Reproductive Sciences, 2013)
Unexplained male infertility (UMI), the inability to reproduce despite having a normal sexual history, physical exam and semen analysis, can have a genetic origin. Currently, few diagnostic tools are available for detecting such genetic abnormalities. Karyotyping and fluorescence in situ hybridization (FISH) are respectively used for chromosomal alterations in somatic cells and sperm aneuploidy assessment. Gene sequencing and mutational analysis have been introduced for identifying specific mutations and polymorphisms. Other approaches to the molecular evaluation of spermatozoa are under investigation, including array comparative genomic hybridization and whole-genome sequencing and non-coding ribonucleic acid arrays. Although treating cytogenetic abnormalities and genetic aberrations is still out of reach, the integration of these novel techniques may unravel hidden genetic defects in UMI. Finally, a deeper understanding of the sperm epigenome might allow the development of therapies based on epigenome modifications. This review focuses on the genetic basis of UMI and highlights the current and future methods for the evaluation of genetic defects as they relate to UMI. Review of the literature was carried out using ScienceDirect, OVID, PubMed and MedLine search engines.